PATRIARCH TIKHON'S COURSE OF STUDIES AND HIS FELLOW STUDENTSATST. PETERSBURG THEOLOGIC ALACADEMY - Krivosheeva N.A. (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The section contains some documents from archpriest Pyotr Bulgakov'sarchives devoted to His Holiness Patriarch Tikhon, a list of his fellow students,memoirs of his studies at St. Petersburg Theological Academy in 1884(1888,letters of His Holiness Patriarch to Father Pyotr Bulgakov from 1890 to 1914,foreign press(cuttings in Russian devoted to His Holiness Patriarch Tikhon. Thedocuments are supplied with voluminous commentaries. (The introductoryarticle, publication and commentaries by N.A. Krivosheeva.)